Factors Affecting EFL Teacher Motivation - Hülya İpek; Müge Kanatlar (Anı Publishing, 2018)
Although it has been suggested that motivated teachers would be more dedicated and effective in teaching/learning process, further studies need to carried out to highlight this issue. Thus, the current study investigated the factors that affect the motivation of foreign language teachers. The study applied a qualitative design with a purposeful sample of 117 English of Foreign Language (EFL) instructors working at a School of Foreign Languages, at a state university in Turkey. Participants were asked to write down and briefly explain the factors that affect their motivation positively and negatively. Content analysis was applied to determine themes from the data. Data was categorized considering the factors affecting teacher motivation reported in the related literature. Results revealed that EFL teachers' motivation is affected by various factors including the teaching environment, the workplace, collegial relations, and students.